White queen : May French-Sheldon and the imperial origins of American feminist identity - Boisseau, Tracey Jean (Indiana University Press, 2004)
Tracey Jean Boisseau's reading of the "White Queen" (which refers to May French-Sheldon's 1891 expedition to East Africa) connects popular notions of American feminism, American national identity, and the reorientation of Euro-American imperialism at the turn of the century